Correlation Between Menstrual Duration with The Incidence of Anemia - Andyarini, Esti Novi; Hidayati, Irul (International Conference on Sustainable Health Promotion, 2018)
Anemia is a situation where the component in the blood, i.e., Hemoglobin (Hb) the number is less than usual. It will be a matter of serious health problems if not immediately addressed. The prevalence of anemia occurrences in Indonesia was 26.4% in women of fertile age group. Adolescence is a time of onset of anemia will be vulnerable, especially young women because every month was experiencing menstruation. The purpose of this research is to know the existence of a correlation between menstrual duration with anemia. The research method used is a crossectional approach with observational. Sampling using accidental side and number of samples 60 respondents. The dependent variable in this study was the incidence of anemia, and the independent variable was the longtime menstrual. Results of the study found a significant relationship between the presence of long menstrual periods with anemia in young women with a value of P = 0.002 P-value where the value (< 0.05). Conclusion there is a relation between menstrual duration with anemic young women. Suggestions in this study are to provide health education and outreach to the young women especially college students to pay more attention to the intake of nutrients with an iron content of more especially during menstruation.